The use of besmart to improve students' self-discipline in community economy course - Baroroh, Kiromim; Prilanita, Yeni Nur; Nurseto, Tejo; Jannah, Nita Maghfiratul (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2023)
The use of e-learning applications in learning needs to consider the potential for improving students' character. This classroom action research was aimed at investigating the use of Besmart e-learning in improving the students' self-discipline in the Community Economy course. The participants of this research were 108 students majoring in Management at the Faculty of Economics, Universitas Negeri Yogyakarta. This study was based on the model by Kemmis and McTaggart, which comprises steps of planning, implementing/acting, observing and evaluating, analyzing, and reflecting. This study was classroom action research. The data were collected in two cycles of the model through questionnaires, observations, interviews, and system monitoring. This study employed triangulation techniques of data source and method to ensure the data validity. The findings show that using e-learning can improve the students' self-discipline. The students' self-discipline was reflected in self-learning materials, participation in the discussion forums, and submitting the assignments. Besmart is not only a learning medium but can also increase student self-discipline and participation in learning. The success factor in this research is not only the learning media but also the skills of lecturers and students to optimize the use of this media.